QTL mapping based on the embryo and maternal genetic systems for non‐essential amino acids in rapeseed (Brassica napus L.) meal. (5th March 2015) - Wen, Juan; Xu, Jian‐Feng; Long, Yan; Wu, Jian‐Guo; Xu, Hai‐Ming; Meng, Jin‐Ling; Shi, Chun‐Hai
Abstract: BACKGROUND: Non‐essential amino acids are a good source of nitrogen and also very important contributors to the metabolic process. Analysis of quantitative trait locus (QTL) simultaneously located on the amphidiploid embryo and maternal plant nuclear genomes for non‐essential amino acid contents in rapeseed meal across different environments was conducive to further clarify the genetic mechanism of seed quality traits. RESULTS: Twenty‐eight QTLs associated with arginine (five QTLs), histidine (four QTLs), glutamic acid (three QTLs), glycine (three QTLs), proline (three QTLs), alanine (four QTLs) and aspartic acid (six QTLs) contents were identified in present study. All of these QTLs had significant additive main effects from embryo and maternal plant nuclear genomes with eight of them showing significant embryo dominance main effects and 12 showing notable QTL × environment interaction effects. Among them, 12 QTLs were major QTLs which could explain 13.27–35.71% of the phenotypic variation. Specially, five QTL clusters associated with several QTLs related to multiple traits were distributed on chromosomes A1, A4, A5, A7 and C2. CONCLUSION: Non‐essential amino acids in rapeseed meal could be simultaneously controlled by the genetic effects from the QTLs which were located on the chromosomes both in the embryo and maternal plant genetic systems. © 2015 Society of Chemical Industry